Derivation and Application of a Tool to Estimate Benefits From Multiple Therapies That Reduce Recurrent Stroke Risk. Issue 5 (May 2020) - Richards, Adam; Jackson, Nicholas J.; Cheng, Eric M.; Bryg, Robert J.; Brown, Arleen; Towfighi, Amytis; Sanossian, Nerses; Barry, Frances; Li, Ning; Vickrey, Barbara G.
Abstract : Background and Purpose—: Lowering blood pressure and cholesterol, antiplatelet/antithrombotic use, and smoking cessation reduce risk of recurrent stroke. However, gaps in risk factor control among stroke survivors warrant development and evaluation of alternative care delivery models that aim to simultaneously improve multiple risk factors. Randomized trials of care delivery models are rarely of sufficient duration or size to be powered for low-frequency outcomes such as observed recurrent stroke. This creates a need for tools to estimate how changes across multiple stroke risk factors reduce risk of recurrent stroke. Methods—: We reviewed existing evidence of the efficacy of interventions addressing blood pressure reduction, cholesterol lowering, antiplatelet/antithrombotic use, and smoking cessation and extracted relative risks for each intervention. From this, we developed a tool to estimate reductions in recurrent stroke risk, using bootstrapping and simulation methods. We also calculated a modified Global Outcome Score representing the proportion of potential benefit (relative risk reduction) achieved if all 4 individual risk factors were optimally controlled. We applied the tool to estimate stroke risk reduction among 275 participants with complete 12-month follow-up data from a recently published randomized trial of a healthcare delivery model that targeted multiple stroke risk factors. Results—: The recurrent stroke risk tool was feasible to apply, yielding an estimated reduction in the relative risk of ischemic stroke of 0.36 in both the experimental and usual care trial arms. Global Outcome Score results suggest that participants in both arms likely averted, on average, 45% of recurrent stroke events that could possibly have been prevented through maximal implementation of interventions for all 4 individual risk factors. Conclusions—: A stroke risk reduction tool facilitates estimation of the combined impact on vascular risk of improvements in multiple stroke risk factors and provides a summary outcome for studies testing alternative care models to prevent recurrent stroke. Registration—: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00861081. Abstract : Supplemental Digital Content is available in the text.